Straightforward synthesis of 4, 5-bifunctionalized 1, 2-oxazinanes via Lewis acid promoted regio- and stereo-selective nucleophilic ring-opening of 3, 6-dihydro-1, 2-oxazine oxides. Issue 45 (8th November 2019) - Huang, Xiu-Rong; Zhang, Yu-Mei; Wan, Ting-Biao; Zhang, Piao; Zhang, Xiu-Xiu; Wang, Fang-Ming; Xu, Defeng; Shen, Mei-Hua; Xu, Hua-Dong
Abstract: Functionalized 1, 2-oxazinanes are interesting and valuable heterocycles with potential applications in synthetic and medicinal chemistry. A straightforward strategy for quick access to unprecedented trans -4-hydroxyl-5-azido/cyano/amino 1, 2-oxazinanes are developed: N-COR 3, 6-dihydro- 1, 2-oxazine oxides are prepared with ease from related dihydro- 1, 2-oxazines and opened by nucleophiles TMSN3, TMSCN and aryl/alkyl amines. Appropriate Lewis acid catalysts are found playing a vital role for both reaction rate and regioselectivity. The N-COR group can be removed under mild conditions to provide highly desirable NH 1, 2-oxazinanes inaccessible via previous methods. Graphical abstract: Lewis acid catalysis enabled highly selective ring-opening of 3, 6-dihydro-1, 2-oxazine oxide with nucleophiles gives rise to valuable functionalized 1, 2-oxazinanes with readily removable N- COR group.Image 1